Cortical cerebrovascular and metabolic perturbations in the 5xFAD mouse model of Alzheimer’s disease - Jullienne, Amandine; Szu, Jenny I.; Quan, Ryan; Trinh, Michelle V.; Norouzi, Tannoz; Noarbe, Brenda P.; Bedwell, Amanda A.; Eldridge, Kierra; Persohn, Scott C.; Territo, Paul R.; Obenaus, Andre (Frontiers in Aging Neuroscience, 2023)
Introduction The 5xFAD mouse is a popular model of familial Alzheimer’s disease (AD) that is characterized by early beta-amyloid (Aβ) deposition and cognitive decrements. Despite numerous studies, the 5xFAD mouse has not been comprehensively phenotyped for vascular and metabolic perturbations over its lifespan. Methods Male and female 5xFAD and wild type (WT) littermates underwent in vivo18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) imaging at 4, 6, and 12 months of age to assess regional glucose metabolism. A separate cohort of mice (4, 8, 12 months) underwent “vessel painting” which labels all cerebral vessels and were analyzed for vascular characteristics such as vessel density, junction density, vessel length, network complexity, number of collaterals, and vessel diameter. Results With increasing age, vessels on the cortical surface in both 5xFAD and WT mice showed increased vessel length, vessel and junction densities. The number of collateral vessels between the middle cerebral artery (MCA) and the anterior and posterior cerebral arteries decreased with age but collateral diameters were significantly increased only in 5xFAD mice. MCA total vessel length and junction density were decreased in 5xFAD mice compared to WT at 4 months. Analysis of 18F-FDG cortical uptake revealed significant differences between WT and 5xFAD mice spanning 4–12 months. Broadly, 5xFAD males had significantly increased 18F-FDG uptake at 12 months compared to WT mice. In most cortical regions, female 5xFAD mice had reduced 18F-FDG uptake compared to WT across their lifespan. Discussion While the 5xFAD mouse exhibits AD-like cognitive deficits as early as 4 months of age that are associated with increasing Aβ deposition, we only found significant differences in cortical vascular features in males, not in females. Interestingly, 5xFAD male and female mice exhibited opposite effects in 18F-FDG uptake. The MCA supplies blood to large portions of the somatosensory cortex and portions of motor and visual cortex and increased vessel length alongside decreased collaterals which coincided with higher metabolic rates in 5xFAD mice. Thus, a potential mismatch between metabolic demand and vascular delivery of nutrients in the face of increasing Aβ deposition could contribute to the progressive cognitive deficits seen in the 5xFAD mouse model.